A Turtle’s Journey: Strengthening Indigenous Research Capacity through Mentoring - Heron Loban (eTropic: electronic journal of studies in the tropics, 2014)
Mentoring can provide significant benefits to both the mentor and the mentee. Such relationships can develop organically, or through a matching process as part of a mentoring program, as structured mentoring. This paper examines the advantages and disadvantages of both types of mentoring in the context of strengthening Indigenous research capacity. The author reflects on her own experiences of being mentored as an Indigenous academic and researcher and the lessons that can be learned from this experience. With reference to the literature and author’s case study, the paper will focus on the potential professional, personal and social impacts of mentoring relationships for Indigenous academics.